MADRASAH BANAT: POTRET PENDIDIKAN ANAK PEREMPUAN NU MASA KOLONIAL BELANDA - Kholid Mawardi (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
In Nahdlatul Ulama at Netherlands colonial era, we cannot find man and woman discrimination on education sector. It isevidenced with the existence of madrasah (school) special for NU’s girl that known as Madrasah Banat. This madrasah established to formloftiest quality woman (al-mar’atu as-shalihah) that ready to serve for next generation progress